PENGARUH OPINI AUDIT, GOING CONCERN, DAN PROFITABILITAS PERUSAHAAN PADA AUDITOR SWITCHING DENGAN FINANCIAL DISTRESS SEBAGAI VARIABEL MODERASI (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2013-2016) - Widya Elisa; Hardi Hardi; Ilham Elfi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2019)
To produce reliable financial reports, the client company is required toconduct audit rotation. The obligation of auditor rotation in Indonesia isregulated by the Indonesian government in the Regulation of the Minister ofFinance of the Republic of Indonesia Number 17 / PMK.01 / 2008 concerning